Making your own luck : from a skid row bar to rebuilding Indiana University athletics - Glass, Fred (Attorney) (Indiana University Press, 2021)
"One man's odyssey from skid row to rebuilding a major collegiate sports program. In Making Your Own Luck, former Indiana University athletic director Fred Glass recounts how even a self-described "knucklehead" learned to be prepared to recognize and seize opportunities and thus make his own luck through life. Growing up in a skid row bar, having an alcoholic father, struggling with anxiety and self-doubt, and making his share of stupid mistakes, Glass had much to contend with in early life. However, supported by socially enlightened parents, a Jesuit education, and his soulmate, Barbara, his odyssey has led him to serve a mayor, a governor, a senator, and even a president. With great humor and insightful reflection, Glass details how he helped keep the Colts in Indianapolis-he spearheaded a massive convention center expansion and the building of Lucas Oil Stadium and even helped to attract the Super Bowl to his hometown. Any of these accomplishments individually would be more than enough to call Glass's career a resounding success, but they were only the beginning. In the latest stage of his journey, Glass led the rebuilding of the athletic program of his beloved alma mater, Indiana University. Featuring a foreword from IU alumnus and owner of the Dallas Mavericks, Mark Cuban, Making Your Own Luck is a must-read not only for Indiana sports fans, but for anyone that recognizes the importance of preparation, opportunity and action in creating your own success"--